Relationship quality in Bangladeshi retail industry - Aziz, Md. Tareque; Azila, Nor (© (2012) IACSIT Press, Singapore, 2016)
This article was published inInternational Proceedings of Economics Development and Research [© 2012 IACSIT Press, Singapore] and the definite version is available at : http://www.ipedr.com/vol38/009-ICEBI2012-A00016.pdf The article website is at: http://ipedr.com/